Aqueous Ammonia Pre-treatment of Wheat Straw: Process Optimization and Broad Spectrum Dye Adsorption on Nitrogen-Containing Lignin - Sipponen, Mika Henrikki; Österberg, Monika (Frontiers in Chemistry, 2019)
Biorefineries need cost-efficient pretreatment processes that overcome the recalcitrance of plant biomass, while providing feasible valorization routes for lignin. Here we assessed aqueous ammonia for the separation of lignin from hydrothermally pretreated wheat straw prior to enzymatic saccharification. A combined severity parameter was used to determine the effects of ammonia concentration, treatment time and temperature on compositional and physicochemical changes (utilizing elemental analysis, cationic dye adsorption, FTIR spectroscopy, size-exclusion chromatography (SEC), and 31P nuclear magnetic resonance (NMR) spectroscopy) as well as enzymatic hydrolysability of straw. Pretreatment at the highest severity (20% NH3, 160 °C) led to the maximum hydrolysability of 71% in a 24 h reaction time at an enzyme dosage of 15 FPU/g of pretreated straw. In contrast, hydrolysabilities remained low regardless of the severity when a low cellulase dosage was used, indicating competitive adsorption of cellulases on nitrogen-containing lignin. In turn, our results showed efficient adsorption of cationic, anionic and uncharged organic dyes on nitrogen-containing lignin, which opens new opportunities in practical water remediation applications.